Particular features as regards the categories of civil servant with policing powers during the Phanariot Rulership - Marin, Marilena; Tătaru, Oana (Technium Social Sciences Journal, 2021)
Our work makes a foray into the history of the police and analyzes categories of civil servants/public officials with police duties, as we find them in the era of the Phanariot rulers. The analysis I made on this subject concerns only the officials from the Romanian countries, without extending the presentation to other medieval countries. The structure of our paper targets public positions and categories of officials, with the specifics of their activity. The original character of the paper consists in the interdisciplinary approach of public functions and police duties, both in terms of public administration history, the history of the Romanian police, but also the English language, for which the archaic Romanian words represented a real challenge.